Optimization Of District-Wide Mine Layout In Multi-Seam Mining: A Case Study - Huamin Li (International Conference on Ground Control in Mining, 2000)
Mine # 8 of Pindingshan Coal Group, Henan Province, China has an annual production 2 million metric tons. But it encounters many problems, e.g. mine layout is complicated, roadway maintenance is difficult, coal and gas outbursts are severe, production cost is high, etc. The major reason was due to the additive effects of abutment pressure interaction of previous mining in D, E, and F seams. At the request of mine management, an in-depth systematic analysis including underground observation, modeling with simulated materials, and photoelastic experimentation was performed to obtain site-specific results which include the dynamic and static influence zones of mining D, E, and F seams, propagation characteristics of abutment pressure in the floor strata, interburden movement caused by undermining, etc.